PENGARUH INTENSITAS CAHAYA DAN DOSIS PUPUK KASCING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAYAM MERAH (Amaranthus tricolor L.) - Hardiane, Ketut; Maryani, Yekti; Kusdiarti, Lilik (JURNAL ILMIAH AGROUST, 2017)
The purpose of this research was to determine the effet of vermicompost dosage the growth and yield of red spinach. This experiment was conducted in the field of Merapi Organic Farm which is located in Balangan Village (Wukirsari, Cangkringan sub district Sleman regency, Yogyakarta). The altitude is about 500 meters above sea level with temperature between 230Câ€“290C and the soil type is regosol. The experiment layed out a complete randomized block design, the experiment arranged in split plot and laid out in randomized complete block design. The main plot wasÂ  light intensity i.e. 100 %, 75% and 65%. The subplot was dosage of vermicompost i.e. 5.0, 7.5 and10 tons per hectare, and each treatment was repeated three times. Variables observed were plant height, number of leaves, leaf area, stem diameter, fresh and dry weight of plant, chlorophyll content and yield per hectare. The results showed that there is no interaction between those two factors on the growth and yield but chlorophyll content. The high intensity of light giving growth and high yield, but vermicompost did not significantly affect the growth and yield of red spinach.